Expanding Mechanisms of Governance: Uncertainty and Risk in Police Decision-Making Strategies in the Pursuit of Specialized Peace Bonds - Ballucci, Dale (Crime & delinquency, 2023)
This study examines police officers? decision-making practices through analyzing how they determine which offenders are candidates for an 810, or peace bond. This legal tool allows police officers to petition the courts for continued surveillance and conditions for offenders postrelease. Little, however, is offered in terms of assessment guidelines on how to make such determinations. As a result, police officers discretionary behaviors and additional legal factors play a key role in these determinations. Our findings advance the idea that ?uncertainty? is the central object to be managed, and further complicate how risk is constructed and mobilized by suggesting that risk assessments result in over-precautionary practices.